Two-Step Adaptive Target Detection Scheme Using Beam-Steering FMCW Radar Sensors - Bong-seok Kim; Young-seok Jin; Jieun Bae; Eugin Hyun (Journal of Electromagnetic Engineering and Science, 2024)
This letter proposes a two-stage adaptive target detection approach using a beam-steered frequency-modulated continuous wave (FMCW) radar sensor. In the first step, coarse estimation was performed using multiple sharped beams, where the presence of a target was determined using only a portion of the sampled beat signals. In the second step, a high-resolution range-Doppler (RD) map was generated using the entire information about the beat signal pertaining to the transmitted beams estimated to contain the target. Angle estimation was accomplished through digital beamforming based on the enhanced RD map. Furthermore, to verify the effectiveness of the proposed algorithm, high-resolution target detection experiments were conducted using a 24-GHz FMCW radar, while complexity reduction was evaluated in terms of the required memory size.